Are Professional Codes of Ethics Relevant for Multicultural Counselling? - Pettifor, Jean L. (Canadian Journal of Counselling and Psychotherapy, 2007)
Pederson's three main criticisms of professional codes of ethics-that they lack a moral philosophical foundation, that their cultural grounding promotes unintentional racism, and that multicultural issues are trivialized-are reviewed. Progressive developments in the codes of ethics of the Canadian Psychological Association and the Canadian Counselling Association in defining moral and ethical principles and in providing an ethical decision-making process are described. New developments within the professions promote increased understanding and sensitivity to cultural diversity while other aspects of society may support unintentional racism. Codes of ethics are relevant in supporting competent multicultural counselling.